1980
DOI: 10.1007/bf00421098
|View full text |Cite
|
Sign up to set email alerts
|

The influence of temperature on the amplitude and frequency components of the EMG during brief and sustained isometric contractions

Abstract: The influence of temperature on the amplitude and frequency components of the EMG power spectra of the surface EMG recorded over the forearm muscles was examined in five male and five female subjects during brief and fatiguing isometric contractions of their handgrip muscles. Brief (3 s) isometric contractions were exerted at tensions ranging between 10 and 100% of each subject's maximum strength while fatiguing contractions were exerted at tensions of 25, 40, and 70% of their maximum strength. The temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
116
3
4

Year Published

1983
1983
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 163 publications
(132 citation statements)
references
References 25 publications
9
116
3
4
Order By: Relevance
“…Our results demonstrated a positive correlation between temperature and EMG median frequency (Petrofsky & Laymon, 2005;Oksa, 2002;BiglandRitchie et al, 1981). This correlation may be explained by changes in the neuromuscular junctions, as changes in the kinetics of Ca ++ influx and acetylcholine (ACh) binding what may influence the formation of the endplate potential (EPP) (Rutkove, 2001).…”
Section: Muscle Temperature and Emg Median Frequencysupporting
confidence: 69%
See 4 more Smart Citations
“…Our results demonstrated a positive correlation between temperature and EMG median frequency (Petrofsky & Laymon, 2005;Oksa, 2002;BiglandRitchie et al, 1981). This correlation may be explained by changes in the neuromuscular junctions, as changes in the kinetics of Ca ++ influx and acetylcholine (ACh) binding what may influence the formation of the endplate potential (EPP) (Rutkove, 2001).…”
Section: Muscle Temperature and Emg Median Frequencysupporting
confidence: 69%
“…tibialis anterior EMG amplitude behaved similar to dorsiflexion force (Petrofsky & Laymon, 2005).The immediately coolinginduced decrease on dorsiflexion force may be explained by the interaction of many factors that include reduced release of calcium from the sarcoplasmic reticulum and the decline of ATP availability, which impairs the cross-bridge formation (Howard et al, 1994;Douris et al, 2003), impairment in the conduction velocity of muscle fibers (Kimura et al, 2003) and acetylcholine (ACh) binding kinetics (Rutkove 2001). Cross et al (1996) reported an immediately reduction in muscle performance after cooling.…”
Section: Dorsiflexion Force and Emg Amplitudementioning
confidence: 82%
See 3 more Smart Citations